2022
DOI: 10.7554/elife.75470
|View full text |Cite
|
Sign up to set email alerts
|

A discrete parasubthalamic nucleus subpopulation plays a critical role in appetite suppression

Abstract: Food intake behavior is regulated by a network of appetite-inducing and appetite-suppressing neuronal populations throughout the brain. The parasubthalamic nucleus (PSTN), a relatively unexplored population of neurons in the posterior hypothalamus, has been hypothesized to regulate appetite due to its connectivity with other anorexigenic neuronal populations and because these neurons express Fos, a marker of neuronal activation, following a meal. However, the individual cell types that make up the PSTN are not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…Therefore, inhibition of PSTN neurons is insufficient to affect baseline food intake. These findings are consistent with a recent report 33 .…”
Section: Inhibition Of Pstn Neurons Attenuates Fear-induced Suppressi...supporting
confidence: 94%
See 3 more Smart Citations
“…Therefore, inhibition of PSTN neurons is insufficient to affect baseline food intake. These findings are consistent with a recent report 33 .…”
Section: Inhibition Of Pstn Neurons Attenuates Fear-induced Suppressi...supporting
confidence: 94%
“…The PSTN plays a key role in the termination of feeding behaviors 38,39 . A recent paper demonstrated that the PSTN plays a critical role in appetite suppression 33 . Therefore, we examined whether the lPB-PSTN pathway modulates feeding behavior by optogenetically activating the lPB terminals in the PSTN.…”
Section: Activation Of the Lpb-pstn Pathway Suppresses Feeding Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from AgRP and POMC neurons, other populations in the hypothalamus also contribute to appetite regulation, including a subset of nucleus of the solitary tract neurons containing cholecystokinin (CCK NTS ) ( 70 ), glutamatergic neurons projecting to PVH in the medial septal complex (MSc) ( 71 ), tachykinin-1 expressing neurons (PSTN Tac1 ) in the parasubthalamic nucleus ( 72 ), steroidogenic factor 1 (SF1) neurons in the ventromedial hypothalamus ( 73 ), and melanin-concentrating hormone-expressing neurons ( 74 ). In addition, progress has also been made in some known appetite-regulating factors like neuropeptide Y (NPY) and orexin with optogenetics ( 75 , 76 ).…”
Section: Optogenetic Findings In Depressive-like Behaviorsmentioning
confidence: 99%